2014
DOI: 10.1371/journal.pone.0100514
|View full text |Cite
|
Sign up to set email alerts
|

Admission Cell Free DNA Levels Predict 28-Day Mortality in Patients with Severe Sepsis in Intensive Care

Abstract: AimThe aim of the current study is to assess the mortality prediction accuracy of circulating cell-free DNA (CFD) level at admission measured by a new simplified method.Materials and MethodsCFD levels were measured by a direct fluorescence assay in severe sepsis patients on intensive care unit (ICU) admission. In-hospital and/or twenty eight day all-cause mortality was the primary outcome.ResultsOut of 108 patients with median APACHE II of 20, 32.4% have died in hospital/or at 28-day. CFD levels were higher in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
68
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(71 citation statements)
references
References 33 publications
1
68
2
Order By: Relevance
“…Cell-free DNA (cfDNA) Measurements cfDNA was measured directly in sera using SYBR Gold Nucleic Acid Gel Staining, according to the fluorometric method published before [32,33]. Briefly, samples were added to a black 96-well plate (Greiner Bio-One).…”
Section: Measurement Of Serum Alt Ast Tbil Tnfα Il-1β and Il-10mentioning
confidence: 99%
“…Cell-free DNA (cfDNA) Measurements cfDNA was measured directly in sera using SYBR Gold Nucleic Acid Gel Staining, according to the fluorometric method published before [32,33]. Briefly, samples were added to a black 96-well plate (Greiner Bio-One).…”
Section: Measurement Of Serum Alt Ast Tbil Tnfα Il-1β and Il-10mentioning
confidence: 99%
“…Furthermore, new diagnostic strategies have been currently under evaluation for potential clinical application including measurement of mitochondrial or cell free DNA by qRT-PCR or by direct fluorescence assays (90,91). Recent studies highlighted the key role of epigenetics in sepsis-associated immune dysfunction, in particular DNA methylation and histone acetylation of inflammatory genes (92,93).…”
Section: Resultsmentioning
confidence: 99%
“…Even though it is difficult to isolate the relationship between cfDNA levels and inflammation from a noninfectious etiology, exclusion of patients with sepsis or pneumonia increased the specificity of this marker for assessing COPDE. In our previous work,24 no association was observed between cfDNA levels and microorganisms or source of sepsis. In the present study, cfDNA was found to be a good clinical marker during a COPDE as observed in other medical conditions 17,19.…”
Section: Discussionmentioning
confidence: 61%
“…Thus, studying cfDNA during a COPDE is an important area of research given that exacerbations are marked by an increased inflammatory response11,12 that is characterized by cell damage and apoptosis 11,13,14. Recently, cfDNA has been investigated as a reliable, novel prognostic marker in a number of disease states such as cancer, trauma, myocardial infarction and sepsis 1524…”
Section: Introductionmentioning
confidence: 99%